Stone Age Magic? Animal-Headed Antler Staffs from Prehistoric Northern Europe as Magical Instruments - Mantere, Ville N. (University of Chicago Press, 2026)
This study investigates the use of animal-headed antler staffs as potential magical instruments in the Stone Age of northern Europe. These staffs are found in both archaeological contexts and rock art, offering unique insights into their diverse uses. Their association with animals, humans, and symbolic power underscores their significance in prehistoric strategies for coping with uncertainty and interacting with the universe. The findings indicate that the animal-headed staffs served various mediating purposes, which can be understood as “magical.” Additionally, this study suggests that Stone Age magic in northern Europe was primarily, though not exclusively, related to human–animal relations.